2013
DOI: 10.1002/cpdd.38
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of a Clinically Significant Effect of Food on the Single Dose Pharmacokinetics of Vorapaxar, a PAR‐1 Antagonist, in Healthy Adult Subjects

Abstract: In this open-label, randomized, 2-period crossover study, 16 healthy subjects received a single oral 2.5-mg dose of vorapaxar in the fed (i.e., standardized high-fat breakfast) and fasted (i.e., an overnight fast) state with a 6-week washout. Plasma samples for vorapaxar assay were obtained pre-dose and up to 72 hours post-dose. Least squares (LS) geometric mean AUC0-72 hr and Cmax were analyzed by ANOVA. If 90% confidence intervals (CI) for the geometric mean ratios (GMRs; fed/fasted) of AUC0-72 hr and Cmax w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Vorapaxar pharmacokinetic parameters are unaffected by food consumption [ 14 , 15 ]. No dosage adjustment is needed for patients with end-stage renal failure [ 16 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Vorapaxar pharmacokinetic parameters are unaffected by food consumption [ 14 , 15 ]. No dosage adjustment is needed for patients with end-stage renal failure [ 16 ].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…However, the differences were not considered clinically significant. 14 An open-label crossover study in 16 healthy volunteers showed that food did not significantly affect the pharmacokinetics of a single oral dose of vorapaxar 2.5 mg. 15 Ethnicity does not seem to affect the pharmacokinetics and pharmacodynamics of vorapaxar. No differences were observed between age-, sex-, height-, and bodyweight-matched Japanese and white volunteers.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 97%
“…The peak plasma concentration occurs within 1–2 hours. 17 , 18 Food has no effect on its oral bioavailability. The mean volume of distribution of vorapaxar is ~424 L. 16 Vorapaxar is primarily metabolized by CYP3A4 and CYP2J2 to an inactive metabolite (M19) and an equally potent active metabolite M20.…”
Section: Pharmacologymentioning
confidence: 99%